Analisis Pemanfaatan AI dalam Komunikais Visual pada Akun Tiktok @ainusantara - Raisha, Raisha Shahana; Detya Wiryany; Maudy Rizkiana Poedjadi (UPT Publikasi Ilmiah UNISBA, 2024)
This article focuses on TikTok social media that uses AI (Artificial intelligence) technology to visualize video content. In this day and age, technology is increasingly sophisticated, one of which is AI technology which plays a major role in creating content in a short time. One of the unique concepts of using AI (artificial intelligence) is the balance to attractively visualize each object in the image. This technology can also edit and create content in the form of videos, images, illustrations, etc. The use of AI in visual communication in video content has a great effect on creating visual aesthetics to be more beautiful and have real color contrasts, and can also provide information with the video without having to use words. This research will also look at the technical description of how AI (Artificial Intelligence) can provide great benefits in providing information through video visualization. To achieve this goal, the researcher uses a qualitative approach method with phenomenology in order to get a comprehensive picture of the object of research. The role of AI in visual communication is expected to provide great benefits and apply it properly through creativity and innovation that comes from human ideas to create interesting images or videos.